The Role of Family in Adaptation to Different Dimensions Following Spinal Cord Injury: A Scoping Review - Yousefpour, Nahid; Sangooni, Hashem (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This scoping review was conducted to identify, describe, and collate the role of the family in various dimensions of adaptation following SCI and to address the current research gaps. Methods and Materials: This study used a scoping review method based on the Arksey and O’Malley framework. Searches were conducted across PubMed, Scopus, Web of Science, Google Scholar, SID, and Magiran using relevant keywords (including the English terms “spinal cord injury”, “family”, “adaptation”, and their Persian equivalents) from inception to October 2025. After 1,023 duplicate articles were removed from the 3,512 identified articles, 2,489 articles were screened based on title and abstract, of which 315 articles were selected for full-text review. Finally, 148 eligible studies were selected for data charting and analysis. Findings: Results highlighted a vital and multifaceted role of the family in the adaptation process of SCI patients. This role is manifested in various dimensions, including emotional and psychological support (e.g., reducing depression and anxiety, increasing hope), practical and caring support (e.g., helping with daily activities, managing physical complications), improving family functioning (e.g., increasing cohesion and problem solving), developing coping skills, and facilitating the rehabilitation process. Additionally, challenges such as caregivers’ financial pressure, inadequate knowledge, and burnout were identified as barriers to adaptation. Conclusion: The family serves as the supportive backbone for SCI patients as they adapt to various aspects of life following injury. However, it seems essential to adopt comprehensive supportive interventions, educate families, address financial challenges, and facilitate access to rehabilitation services. It is suggested that future researchers focus on the effects of family-centered interventions and the role of cultural factors and perform longitudinal studies in this area.